Catholic nuns and sisters in a secular age : Britain, 1945-90 - Mangion, Carmen M. (Gender in history., 2020)
This is first in-depth study of post-war female religious life. It places Catholic sisters and nuns at the heart of the turbulent 1960s and integrates their story of social change into a larger British and international one, thus displaying how religious bodies engaged in modernisation. It addresses themes relevant to the 1960s such as the Modern Girl and youth culture, '1968', generational discourse, post-war modernity, the voluntary sector and the women's movement. Though rooted in the experiences of women religious in Britain, the book probes transnational relationships and global interconnectivities between women religious within and across national divides. These women were at the forefront of the Roman Catholic Church's movement of adaptation and renewal towards the world, and this volume tells their stories in their own words.